COVID-19 outbreak and increased risk of amblyopia and epidemic myopia: Insights from EUROCOVCAT group. Issue 1 (January 2022) - Toro, Mario Damiano; Bremond-Gignac, Dominique; Brézin, Antoine Pierre; Cummings, Arthur Bernard; Kemer, Ozlem Evren; Kermani, Omid; Malyugin, Boris Edvard; Prieto, Isabel; Teus, Miguel Angel; Tognetto, Daniele; Zweifel, Sandrine; Rejdak, Robert
The most common cause of vision impairment in children is amblyopia. It is defined as impaired visual acuity in one or both eyes that is present with no demonstrable abnormality of the visual pathway and is not immediately resolved by wearing glasses. After the World Health Organization (WHO) recognized COVID-19 as a global pandemic on March 11, 2020, widespread changes and restrictions to social and sanitary practices have presented significant issues in access to eye care during the COVID-19 pandemic. A reduction of more than 80% in pediatric eye care volume up to its total cessation has been observed in different departments. In this scenario, reduced or absent eyesight, due to delay in timely treatment of amblyopic conditions, could create major, long-lasting effects on all aspects of life, including daily personal activities, interacting with the community, school and work opportunities and the ability to access public services. Processes coming out of lockdown should be gradually easing restrictions giving priority to ophthalmology and eye care facilities so that amblyopia does not remain unattended and irreversible as in adults due to lack of timely treatments. If not reversible, this process could lead to a dramatic increase in disability and unsustainable social costs for many governments.